Exercise training: types and methods, role in disease prevention and health benefits (Sports and athletics preparation, performance, and psychology, 2015)
Exercise is one component of daily energy expenditure in humans. It has become an important part of healthy lifestyles, because individuals are less active both at work and at home compared to earlier days and because today`s environment makes it easy for individuals to be inactive, such as when people use elevators instead of stairs, cars instead of bicycles, and technology instead of activities with full body movement. This book discusses the types and methods of exercise training, as well as the role it plays in disease prevention. (novinka)